Effects of aquatic and land high intensity interval training on hemodynamics and vascular function of middle-aged men - Xin, Chenxi; Fu, Jiahao; Zhou, Zhihui; Zhou, Yujiao; He, Hui (Frontiers in Physiology, 2024)
Objective: To investigate the effects of 8-week aquatic and land high intensity interval training (HIIT) on hemodynamics and vascular function in middle-aged men. Methods: Thirty middle-aged men were selected and divided into 15 men (52.43±4.11) in aquatic and 15 men (52.74±5.62) in land group by random number table. They performed HIIT in aquatic and land 3 times a week for 8 weeks. Pre-test, inter-test and post-test respectively measure hemodynamics and vascular function. Results: (1) Body composition: After 8 weeks of exercise, weight, body mass index (BMI) and body fat rate (BF) were lower than before exercise (aquatic group: P<0.01, land group: P<0.05). The improvement of BF in the aquatic group was better than that in the land group (P<0.05); (2) Cardiac function: After 8 weeks of exercise, stroke volume (SV), left ventricular end-diastolic volume (EDV), cardiac output (CO), and left ventricular fractional shortening (FS), were higher than before exercise (aquatic group: P<0.01, land group: P<0.05), heart rate (HR) and left ventricular end-systolic volume (ESV) were lower than before exercise (aquatic group: P<0.01, land group: P<0.05). The improvement of SV, HR, EDV, ESV, CO and FS in the aquatic group was better than that in the land group (P<0.05); (3) Hemodynamics: After 8 weeks of exercise, systolic blood pressure (SBP), diastolic blood pressure (DBP) were lower than before exercise (aquatic group: P<0.01, land group: P<0.05), wall shear stress (WSS) and peak systolic velocity (PSV) were higher than before exercise (aquatic group: P<0.01, land group: P<0.05). The improvement of SBP, WSS and PSV in the aquatic group was better than that in the land group (P<0.05); (4) Vascular function: basal diameter and flow-mediated dilatation (FMD) level in aquatic and land group was higher than before exercise, pulse wave velocity (PWV) level was lower than before exercise (aquatic and land group: P<0.05). The improvement of FMD in the aquatic group was better than that in the land group. Conclusion: The body composition, hemodynamics and vascular function of middle-aged men were improved by 8-week aquatic and land HIIT. Aquatic HIIT has better effect on body fat rate, hemodynamics and flow-mediated dilatation in middle-aged men.